Bone marrow adipose tissue expansion and bone loss in experimental chronic kidney disease is independent of altered bone marrow stromal cell lineage determination - Promruk, Worachet; Cawthorn, William P.; Bourne, Lucie E.; Jayash, Soher N.; Pears, Aine; Staines, Katherine A.; Stephen, Louise A.; Farquharson, Colin (Frontiers in Endocrinology, 2025)
IntroductionChronic kidney disease-mineral bone disorder is the irreversible loss of kidney function leading to altered mineral homeostasis and bone loss, commonly referred to as renal osteodystrophy. Bone marrow adipose tissue (BMAT) accumulates in clinical CKD and animal models of this disease, but the mechanism(s) responsible are unclear. This study sought to determine the relationship between BMAT distribution and bone structure and to establish whether disease progression directly affected: 1) the commitment of bone marrow mesenchymal stromal cells (BMSCs) to osteoblastic (OPC) and adipogenic (APC) precursor cells, and 2) the differentiation of BMSCs to mature adipocytes and osteoblasts.MethodsEight-week-old male C57BL/6J mice received a diet supplemented with 0.2% adenine for ≤5 weeks to induce CKD. Control mice received the same diet without adenine. Serum biochemistries were quantified using a biochemistry analyzer and plasma hormone levels by ELISA. Bone phenotypes were evaluated by µCT. The same bones were decalcified and stained with 1% osmium tetroxide and BMAT quantified using µCT. Precursor cell populations in bone marrow were quantified by flow cytometry.ResultsThe development of CKD during the early stages of the disease was confirmed by elevated serum concentrations of blood urea nitrogen and creatinine from 3-weeks’ induction. After 5-weeks’ induction, trabecular bone microarchitecture including bone mineral density was compromised whereas cortical bone area and thickness were decreased in CKD tibiae after 3- and 5-weeks’ induction. Compared to age-matched controls, proximal tibial BMAT tended to increase in CKD mice by 3 weeks’ induction and this reached statistical significance after 5-weeks where there was a negative correlation between regulated BMAT accumulation and trabecular bone loss. BMAT accumulation was not due to calorie deficiency and was positively correlated with circulating adiponectin, but not with circulating leptin or corticosterone. During CKD onset (weeks 1-2) of CKD, BMSCs from CKD mice had enhanced adipogenic potential but the proportions of OPCs and APCs within the bone marrow were unchanged.ConclusionsIn experimental CKD, BMAT expansion depends on CKD duration and does not appear to be driven by hypoleptinemia or hypercorticosteronemia, or by altered precursor cell differentiation during CKD onset.